The Educational System and the Reproduction of Social Structures: A Sociological Approach to the Mechanisms of Symbolic Domination in Pierre Bourdieu’s Thought (The International Journal for Scientific Research, 2026)
This article takes as its point of departure a critical inquiry into the role played by the educational institution within the broader social structure, particularly insofar as it may contribute to the reproduction of social inequalities and the consolidation of relations of symbolic domination. Accordingly, the article seeks to examine the nature of the role assumed by the educational institution in reproducing the existing social order, through an analysis of the symbolic and cultural mechanisms deployed by the educational system to perpetuate social inequalities and confer legitimacy upon them. This analysis is grounded in the theoretical perspective developed by Pierre Bourdieu.To achieve this aim, the article is structured around two main axes. The first is devoted to the conceptual framework of the theory of reproduction, while the second examines and analyses the mechanisms through which the educational system reproduces the values of domination and inequality that sustain social disparities.The article concludes that reproduction operates as a strategy through which the dominant order preserves the prevailing relations of power within society. In this process, the educational institution functions as an ideological instrument for reproducing the domination of the ruling class and reinforcing social inequality. The educational institution is thus transformed into a concealed instrument of domination, playing a decisive role in legitimizing the culture of the dominant class and presenting it as high culture.
Keywords: educational system; reproduction; educational institution; symbolic domination; social structures